2005
DOI: 10.1007/11556114_29
|View full text |Cite
|
Sign up to set email alerts
|

Memory for Spatial Location: Influences of Environmental Cues and Task Field Rotation

Abstract: Abstract. We developed a formal theoretical extension of the categoryadjustment model (Huttenlocher, Hedges, & Duncan, 1991) to incorporate the potential impact of external reference cues in spatial memory. This extension was tested in an experiment in which individuals remembered locations within a circular task field, with different numbers of peripheral cues available. Orientation of the task field was dynamic in the sense that it was rotated on the majority of trials. By modeling the angular bias shown in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
24
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5
1
1

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 11 publications
6
24
0
Order By: Relevance
“…These effects were well predicted by an extension of the previously developed flexible fuzzy-boundary model (Fitting et al, 2005;Wedell et al, 2007). Bias measures early and late in the navigational process reflected a shift in remembered locations in the direction toward the nearest available external cue.…”
Section: Key Findingssupporting
confidence: 54%
“…These effects were well predicted by an extension of the previously developed flexible fuzzy-boundary model (Fitting et al, 2005;Wedell et al, 2007). Bias measures early and late in the navigational process reflected a shift in remembered locations in the direction toward the nearest available external cue.…”
Section: Key Findingssupporting
confidence: 54%
“…In previous research (Fitting et al, 2005, in press) we have demonstrated that when field rotation is absent, memory for spatial location in the classic dot location procedure is largely cue-independent rather than cue-dependent. This occurs even when ample peripheral cues are available.…”
Section: Discussionmentioning
confidence: 72%
“…The former model is referred to as the fixed-quadrants fuzzy-boundary model and the latter as the cue-based fuzzyboundary model. In this paper we will focus on the cue-based fuzzy-boundary model (for detailed description of the fixed-quadrants fuzzy-boundary model, see Fitting, Wedell, & Allen, 2005;.…”
Section: Prior Model Developmentmentioning
confidence: 99%
“…The model we use is based on our earlier work (Fitting, Wedell, & Allen, 2005, in which we extended Huttenlocher et al's (1991) category-adjustment model in two basic ways. First, the model included parameters that reflect the tendency to recruit prototypes from adjacent categories in making estimates of targets located near a boundary.…”
Section: Fuzzy-boundary Model For Inferring Spatial Categoriesmentioning
confidence: 99%